2017
DOI: 10.1080/03043797.2017.1298569
|View full text |Cite
|
Sign up to set email alerts
|

Formative assessment to develop oral communication competency using YouTube: self- and peer assessment in engineering

Abstract: Obtaining oral communication competency is an important skill for engineering students to prepare them for interacting and working in any professional setting. For engineers, it is also important to be able to present technical information to non-technical audiences. To ensure oral competency, a non-graded formative assessment approach using video with self-and peer assessment was introduced into a final-year engineering thesis course. A low workload approach was used due to growing student numbers and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…provided. This provides further support to research focused on self-efficacy and mindset that value of learning impacts a student's perception of difficulty and their approach and motivation to learn (Lahtinen et al 2005;Tek et al 2018) and as a result the students that are most in need of support structures are the ones less likely to take advantage of them (Nikolic and Raad 2017;Nikolic et al 2018). The relationship that relevance plays in motivating students to learn programming is possibly best seen within the civil and mining data;…”
Section: Resultsmentioning
confidence: 62%
“…provided. This provides further support to research focused on self-efficacy and mindset that value of learning impacts a student's perception of difficulty and their approach and motivation to learn (Lahtinen et al 2005;Tek et al 2018) and as a result the students that are most in need of support structures are the ones less likely to take advantage of them (Nikolic and Raad 2017;Nikolic et al 2018). The relationship that relevance plays in motivating students to learn programming is possibly best seen within the civil and mining data;…”
Section: Resultsmentioning
confidence: 62%
“…Not long after Charlie Ginsburg invented the video recorder in 1951 (Fukkink, Trienekens, & Kramer, 2011), video-recording was used for educational purposes to permit students to watch and assess their performance (Ritchie, 2016). As reliance on technology has increased, literature has continued to indicate that the use of video recording during communication has been found across many disciplines to be an effective way to help students adopt and learn from the observers' perspective (Hamilton, 2012;Guo, 2013;Nikolic, Stirling, & Ros, 2018).…”
Section: The Use Of Video To Improve Oral Communication Skillsmentioning
confidence: 99%
“…Reviewing prior empirical research indicates that use of video recording has been found by many disciplines for many years to be an effective technique to help students evaluate and improve their oral presentation skills (Hamilton, 2012;Guo, 2013;Nikolic, Stirling, & Ros, 2018). Video recordings contribute positively to improve the student's learning if they are accompanied by an opportunity for the student to self-critique and provide their feedback (Paul, Dawson, Lanphear, & Cheema, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer evaluation in the middle of the project also helps students to improve their team's performance [13]. Many researchers who have investigated the use of peer evaluations in engineering course [14]- [17] concluded that peer and self-evaluations increase student's teamwork skills [18] and motivate students to collaborate for the same teamwork goal [19]. CATME's peer evaluation framework includes five validated teamwork behavior dimensions: Contributing to the team's work, Interacting with teammates, Keeping the team on the track, Expecting quality, and Having relevant knowledge, skills, and abilities (KSAs).…”
Section: Introductionmentioning
confidence: 99%